Experimental Pasteurella haemolytica infection in sheep - KAMIL, S A; PARMAR, N S; KALICHARAN, KALICHARAN; KUMAR, P N; NAIK, D (The Indian Journal of Animal Sciences, 2013)
Pneumonia wag induced experimentally in 15 adult healthy male sheep using 20 ml of Pasteurella haemolytica type A culture intratracheaUy with the help of flexible fiberoptic bronchoscope. The animals exhibited typical signs of pneumonia especially those which died spontaneously. A rising trend in thevalues of total erythrocyte count, haemoglobin and packed-cell volume was observed. There was evidence of neutrophilia with corresponding lymphocytopenia. Biochemical values were within the normal limits. Bronchoscopic observations revealed deeper colouration of bronchial mucosa and bronchoalveolar larvage and reduced recovery of the latter. Cytology of the larvage fluid revealed increase in the number of neutrophils with corresponding decrease in lymphocytes. Brush and biospy specimens revealed practically similar pictures as bronchoalveolar larvage. Pneumonic lesions were more severe in later stages as well as in the animal succumbing to disease. The lesions occurred more frequently and in large areas on right side. The areas of consolidation occasionally revealed necrotic, suppurative or gangrenous foci with or without fibrinous pleurisy. Microscopically acute bronchopneumonia progressively with necrotising changes was the predominant finding along with the occurrence of serous or sorofibrinous exudate. Oat-cell masses in wavy pattern characteristic of pneumonic pasleurellosis occurred after day 10 of infection.